Indigenous Tourism Concept of Building Friendly Tourism for Indigenous Baduy People: Literature Study - Rida Aulia; Retno Kusumastuti (Budapest International Research and Critics University, 2022)
Indigenous tourism has not become a priority approach in encouraging the tourism potential of the Baduy community which is managed by tourism stakeholders. Limited studies on the concept of indigenous tourism have made local parties focus only on promoting their culture and natural environment. This article aims to find out 1) how the steps of Lebak Regency tourism stakeholders in managing Baduy tourism through the indigenous concept. The research method was carried out qualitatively, through literature study. The results show that indigenous tourism is relevant as an alternative approach in managing cultural tourism that is friendly to the environment of the Baduy indigenous people. And the main key to indigenous tourism in Baduy lies in the management of control on the environment, community, industry and appropriate marketing strategies to harmonize environmental and Baduy culture conservation issues which have not been the focus of local governments.